2013
DOI: 10.1371/journal.pone.0069864
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Phenotypes of Human TDP-43 Transgenic Mouse Models Are Independent of Downregulation of Mouse Tdp-43

Abstract: Tar DNA binding protein 43 (TDP-43) is the major component of pathological deposits in frontotemporal lobar degeneration with TDP-43 inclusions (FTLD-TDP) and in amyotrophic lateral sclerosis (ALS). It has been reported that TDP-43 transgenic mouse models expressing human TDP-43 wild-type or ALS-associated mutations recapitulate certain ALS and FTLD pathological phenotypes. Of note, expression of human TDP-43 (hTDP-43) reduces the levels of mouse Tdp-43 (mTdp-43). However, it remained unclear whether the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
(86 reference statements)
4
8
0
Order By: Relevance
“…In line with previous studies [25,26], we found a decrease in the levels of the splice variant of sortilin 1 with exon 17b inclusion (Sort1 + Ex17b) in the TDP-43 (A315T) mice (Figure 3F). Since it has been shown [25,26] that downregulation of TDP-43 in mouse N2a cells, leads to an increase in Sort1 + Ex17b levels, this suggests that the human TDP-43(A315T) overexpression can compensate for the downregulation of mouse TDP-43.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies [25,26], we found a decrease in the levels of the splice variant of sortilin 1 with exon 17b inclusion (Sort1 + Ex17b) in the TDP-43 (A315T) mice (Figure 3F). Since it has been shown [25,26] that downregulation of TDP-43 in mouse N2a cells, leads to an increase in Sort1 + Ex17b levels, this suggests that the human TDP-43(A315T) overexpression can compensate for the downregulation of mouse TDP-43.…”
Section: Resultssupporting
confidence: 93%
“…This leads to decreased expression of endogenous TDP-43 due to the 3-fold overexpression of exogenous TDP-43 [15]. Since we and others [25,26] measured a decrease of Sort1 + Ex17b in the brain of human TDP-43 (A315T) overexpressing mice, in contrast to the upregulation seen in mouse N2a cells with TDP-43 knock-down, this suggests that the reduction of endogenous TDP-43 is overcompensated by the expression of human mutant TDP-43 (A315T) . As suggested previously [10,23,24], the downregulation of endogenous TDP-43 can contribute to the pathogenesis of neurodegeneration, but so does overcompensation, since a physiological range of expression, below or above which pathology develops, appears to be important.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that loss of endogenous TDP-43 protein is accompanied by an increase in the ratio of TDP-43γ:TDP-43 α (i.e., decreased α-splicing), and an increase in TARDBP transcript encoding full-length TDP-43. These two observations are compatible with data from numerous models in vivo and in vitro (Ayala et al 2011;Igaz et al 2011;Avendaño-Vázquez et al 2012;Xu et al 2013;D'Alton et al 2014), which show reduction of TARDBP/Tardbp transcript levels in response to exogenous TDP-43 expression. In our studies, the increase in TARDBP transcript did not result in increased levels of TDP-43 protein; in fact, cells overexpressing H5 strongly trended toward reduced TDP-43 protein.…”
Section: Discussionsupporting
confidence: 90%
“…6F), further demonstrating that TDP-43 does not regulate α-splicing of all transcripts. As overexpression of TDP-43 in vivo and in vitro leads to decreased TARDBP transcript and TDP-43 protein levels (Ayala et al 2011;Igaz et al 2011;Xu et al 2013;D'Alton et al 2014), and that increased α-splicing is implicated in this process (Ayala et al 2011;Polymenidou et al 2011;Avendaño-Vázquez et al 2012), we examined the effect of loss of functional, nuclear TDP-43 and concomitant increase in the TDP-43γ:TDP-43α ratio on TARDBP transcript levels. Using primers that detect all transcripts that encode full-length TDP-43, we observed a doubling of TARDBP transcript in cells overexpressing H5 relative to controls (NRQ empty vector = 0.69 ± 0.04, NRQ myc-H5 = 1.46 ± 0.12, N = 5 per group, P = 0.0003) (Fig.…”
Section: Sequestration Of Tdp-43 Is Accompanied By Tardbp Dysregulationmentioning
confidence: 99%
“…The autoregulatory capacity of TDP43 and FUS also represents a potential caveat for investigations involving their overexpression, as the subsequent downregulation of endogenous protein might cause toxicity [147], and confound the interpretation of changes in gene expression or splicing induced by overexpression. Still, exogenously expressed TDP43 is functional and can compensate for endogenous TDP43 deficiency [148], arguing against neurodegeneration due to loss of endogenous TDP43 in overexpression models.…”
Section: Alternative Rna-based Mechanismsmentioning
confidence: 99%